Strategi Pengembangan Ekowisata Mangrove - Firjatullah Divia Arsyalina; Eppy Yuliani (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
The development of coastal and marine ecotourism must consider two aspects, namely the tourist destination aspect and the market aspect. Even though in its development it adheres to the concept of products and markets, the development of tourism products still ensures the preservation of natural and cultural resources of coastal and marine communities. Nowadays, ecotourism in mangrove forests is seen as being able to synergize with real conservation measures for the mangrove forest ecosystem. The potential of mangroves can be used as a tourist attraction as well as an effort to rehabilitate and conserve mangrove areas. The aim of writing this article is to find out the strategy for developing ecotourism, especially mangrove ecotourism, which is based on previous case study research. From the three case studies, it can be concluded that the ecotourism development strategy is determined by analyzing the conditions and feasibility of ecotourism.